Chemical oxidative and solid state synthesis of low molecular weight polymers for organic field effect transistors - Mahale, Rajashree Y.; Dharmapurikar, Satej S.; Chini, Mrinmoy Kumar (Chemical Physics Letters, 2018)
Solution processability of the precursor molecules is a major issue owing to their limited solubility for the synthesis of conjugated polymers. Therefore, we favour the solvent free solid state chemical oxidative polymerization route for the synthesis of diketopyrrolopyrrole (DPP) based donor-acceptor (D-A) type conjugated polymers. D-A type polymer Poly(S-OD-EDOT) which contains DPP coupled with EDOT donor units is synthesized via solid state polymerization method. The polymer is employed as an active layer for organic field-effect transistors to measure charge transport properties. The Polymer shows good hole mobility 3.1 x 10(-2) cm(2) V-1 s(-1), with a on/off ratio of 1.1 x 10(3). (C) 2018 Elsevier B.V. All rights reserved.